Impact of pH, nutrient, and salinity stress on lipid synthesis in Coelastrella sp. for sustainable biodiesel production - Suresh Arumugham; Fuad Ameen; Sagaya John Paul Joseph; Praveen Kumar Ramasamy; Thajuddin Nooruddin; Nagaraj Subramani (Discover Applied Sciences)
Highlights Coelastrella sp. demonstrated strong lipid production potential, especially at pH 7.0 and 0.5% fertilizer concentration. Stress conditions enhanced lipid accumulation, indicating resilience and adaptability for cultivation. The fatty acid profile supports the use of Coelastrella sp. for sustainable biodiesel production.